2004
DOI: 10.1007/s00425-003-1189-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of three genes encoding starch synthase�II in rice

Abstract: Three starch synthase (SS) genes, OsSSII-1, OsSSII-2 and OsSSII-3, were identified in rice (Oryza sativa L.) and localized to chromosomes 10, 2 and 6, respectively. The three OsSSII full-length cDNAs were cloned, and the predicted amino acid sequences were found to share 52-73% similarity with other members of the plant SSII family. The SS activity of each OsSSII was confirmed by expression and enzyme activity assay in Escherichia coli. Expression profile analysis revealed that OsSSII-1 was expressed in endosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 23 publications
1
34
0
1
Order By: Relevance
“…3B). The predicted molecular mass of rice SSI calculated from the DNA sequence of the gene coding for the SSI mature protein is 65 kD (Baba et al, 1993;Jiang et al, 2004), which is smaller than the apparent molecular mass (71 kD) estimated on SDS-PAGE. Similar differences in molecular mass were also reported for SSI proteins from maize and potato tubers (Edwards et al, 1995).…”
Section: Characterization Of Ssi In Developing Rice Endospermmentioning
confidence: 62%
“…3B). The predicted molecular mass of rice SSI calculated from the DNA sequence of the gene coding for the SSI mature protein is 65 kD (Baba et al, 1993;Jiang et al, 2004), which is smaller than the apparent molecular mass (71 kD) estimated on SDS-PAGE. Similar differences in molecular mass were also reported for SSI proteins from maize and potato tubers (Edwards et al, 1995).…”
Section: Characterization Of Ssi In Developing Rice Endospermmentioning
confidence: 62%
“…In this region, we observed multiple genes associated with eating quality (e.g., starch synthase IIa; SSIIa; Jiang et al 2004) and heading date [e.g., Hd3a and Hd3b ]. Moreover, other genes controlling these traits were found near this cluster.…”
Section: Distribution Of Qtl Clusters In the Rice Genome Mapmentioning
confidence: 99%
“…In particular, maize contains two isoforms, namely, SS2a and SS2b (Harn et al 1998), and three isoforms are found in the rice genome, SS2-1, SS2-2, and SS2-3 (Hirose and Terao 2004;Jiang et al 2004). Like the SS1 from potato and rice, the latter isoforms are differentially expressed in leaves and storage organs (Harn et al 1998;Jiang et al 2004). Indeed, maize SS2b or rice SS2-2 are expressed in leaves, while maize SS2a or rice SS2-3 are expressed in the endosperm (Harn et al 1998;Jiang et al 2004).…”
Section: Starch Synthases Involved In Amylopectin Synthesismentioning
confidence: 96%
“…Like the SS1 from potato and rice, the latter isoforms are differentially expressed in leaves and storage organs (Harn et al 1998;Jiang et al 2004). Indeed, maize SS2b or rice SS2-2 are expressed in leaves, while maize SS2a or rice SS2-3 are expressed in the endosperm (Harn et al 1998;Jiang et al 2004). On the other hand, rice SS2-1 is expressed in both types of organs during the whole life cycle, whereas other isoforms are expressed at different stages of development (Jiang et al 2004).…”
Section: Starch Synthases Involved In Amylopectin Synthesismentioning
confidence: 98%
See 1 more Smart Citation